Políticas Públicas e educação para pessoas jovens e adultas em situação de privação de liberdade no Amazonas: regulação da sociedade e antagonismos de Direitos Sociais - (:unkn) unknown (Universidade Federal do Amazonas, 2018)
The public policies and the right to education of persons deprived of freedom involves paradigms of rationality in modern society. The interdiscursivity, situationality and dissidences about public policies, in the perspective of social inclusion, reveal a historical problem of the growth of incarceration, social exclusion, denial of education and minimization of rights guarantees, derived from the liberal/neoliberal capitalist ideology. The question of incarceration is delineate by the anemia of political, economic and social conditions in a scenario of economic globalization, power relations and social control, which affect the supply or negation of education in the Amazonas prisions. Discussion of the problem by the work of the researcher, who situates these processes through the analysis of policies, discourses and actions mediated by the local and global state in society, in face of the current symbolic legislation. The objects of the research were the education policies of young people and adults deprived of liberty in Amazonas, the historical forms of regulation of society and the antogonisms of social rights. On which the dialogues with Max (2016), Baudrillard (2015), Bourdie (2014), Julião (2017), Onofre (2014), Hall (2015), Arroyo (2013), Mészáros (2005), Wacquant (2011) were constituted as a means for the analysis of public policies and social inclusion. Historical-dialectical metologogy grounded the examination of the concepts of the whole and the parts that composed reality, and allowed the appropriation of the concrete thought (Marx, 2016). For the construction of the reflection, the discussions started from the quantitative approach, which expressed the reading of real discourses, discourses produced, numerical and social interpretation of education and their processes of social inclusion/exclusion. The documentary research, through direct observation and participant in the spaces of incarceration, provided statistical data, laws, decrees and reports relevant to the analysis of social inclusion / exclusion processes. The study aimed to analyze the mentality that underlies the prison system in contemporary society, its movements and its sustainability, as well as interdiscursivity and situationality about public policies. The results point out that the mentality that underlies the prison system lies in the simulation of a globalized freedom policy, which is imprisoned and controlled physically, virtual and culturally with economic and social implications. The State, mediated by the neoliberal logic, presents itself as a producer of consensuses that generate a social reorganization operated by symbolic and flexible legislation. Young people and adults deprived of liberty in the Amazonas, as amazonics subjects, become fragmented and dumped from their condition of subjects, being coated in the condition of individuals, for which the right to education and freedom are camouflaged by social inclusion policies. Education in the Amazonas and prisons requires, in addition to historical analysis, the analysis of interdiscursivity and political, economic, cultural and identity situationality, in order to strengthen social ills that simulate inclusion policies, but imply social exclusion of a popular education that instrumentalizes social emancipation.

Las políticas públicas y el derecho a la educación de personas privadas de libertad envuelven paradigmas de racionalidad de la sociedad moderna. La interdiscursividad, situacionalidad y disidencias sobre las políticas públicas, en la perspectiva de la inclusión social, develan un problema histórico de crecimiento del encarcelamiento, de la exclusión social, de la denegación de la educación y de minimización de garantías de derechos, oriundos de la ideología liberal/neoliberal capitalista. El tema del encarcelamiento se presenta delineado por la debilidad de las condiciones políticas, económicas y sociales en un escenario de globalización de la economía, relaciones de poder y control social, que incurren en la oferta o denegación de la educación en los presidios de Amazonas. De ahí que, por lo tanto, adviene el debate del problema por el trabajo del investigador, que sitúa estos procesos por medio del análisis de las políticas, discursos y acciones mediadas por el Estado local y global en la sociedad, ante a la legislación simbólica en vigor. Los objetos de la investigación fueron las políticas de educación de personas jóvenes y adultas privadas de libertad en Amazonas, los medios históricos de regulación de la sociedad y los antagonismos de derechos sociales, sobre los cuales los diálogos con Marx (2016), Baudrillard (2015), Bourdieu (2014), Julián (2017), Onofre (2014), Hall (2015), Arroyo (2013), Mészáros (2005), Zaffaroni (2014), Wacquant (2011) se constituyeron como recursos para el análisis de las políticas públicas y inclusión social. La metodología histórico-dialéctica fundamentó el examen de los conceptos del todo y de las partes que compusieron la realidad, y permitieron la apropiación del pensamiento concreto (MARX, 2016). Para la construcción de la reflexión, las discusiones partieron del abordaje cuanti-cualitativo, que expresó la lectura de discursos reales, de discursos producidos, de la interpretación numérica y social de la educación y sus procesos de inclusión/exclusión social. La investigación documental, a través de la observación directa y participante en los espacios de encarcelamiento, suministró datos estadísticos, leyes, decretos e informes oportunos al análisis de los procesos de inclusión/exclusión social. La investigación objetivó analizar la mentalidad que fundamenta el sistema carcelario en la sociedad contemporánea, sus movimientos y su sostenibilidad, así como la interdiscursividad y situacionalidad sobre las políticas públicas. Los resultados apuntan que la mentalidad que sostiene el sistema carcelario se ubica en la simulación de una política de libertad globalizada, la cual se hace arrestada y controlada física, virtual y culturalmente con implicaciones económicas y sociales. El Estado, mediado por la lógica neoliberal, se presenta como productor de consensos que generan un reordenamiento social operado por legislación simbólica y flexible. Los jóvenes y adultos privados de libertad en Amazonas, mientras sujetos amazónicos, se convierten en fragmentados y despojados de su condición de sujetos, siendo recubiertos de la condición de individuos, para los cuales el derecho a la educación ya la libertad son disimulados por políticas de inclusión social. La educación en la Amazonía y en los espacios carcelarios necesita, por tanto, además de análisis histórico, de análisis de la interdiscursividad y de la situacionalidad política y económica, cultural e de identidad, para entonces reforzar el combate a los males sociales que simulan políticas de inclusión, pero que involucran exclusión social en favor de una educación popular que equipa la emancipación social.
Public policies and education for young people and adults in situations of deprivation of liberty in the Amazonas: regulation of society and antagonisms of social rights.
Políticas públicas y educación para personas jóvenes y adultas en situación de privación de libertad en Amazonas: regulación de la sociedad y antagonismos de derechos sociales.
Keywords: Políticas Públicas; Educação de Jovens e Adultos; Privação de liberdade; Inclusão social e educacional; Direito à educação; CIÊNCIAS HUMANAS: EDUCAÇÃO: ADMINISTRAÇÃO EDUCACIONAL: ADMINISTRAÇÃO DE SISTEMAS EDUCACIONAIS